Consensus building on definitions and types of child maltreatment to improve recording and surveillance in Europe: protocol for a multi-sectoral, European, electronic Delphi study - Alison Mary Kemp; Lisa Hurt; Ulugbek Nurmatov; Laura Elizabeth Cowley; Aideen Naughton; Geoff Debelle; Luciana Caenazzo; Gabriel Otterman; Andreas Jud; Leonor Bettencourt Rodrigues; Ravit Alfandari; Diogo Lamela; et al. (BMJ Open)
Introduction Child maltreatment (CM) is a complex global public health issue with potentially devastating effects on individuals’ physical and mental health and well-being throughout the life course. A lack of uniform definitions hinders attempts to identify, measure, respond to, and prevent CM. The aim of this electronic Delphi (e-Delphi) study is to build consensus on definitions and types of CM for use in surveillance and multi-sectoral research in the 34 countries in the Euro-CAN (Multi-Sectoral Responses to Child Abuse and Neglect in Europe) project (COST Action CA19106).Methods and analysis The e-Delphi study will consist of a maximum of three rounds conducted using an online data collection platform. A multi-disciplinary expert panel consisting of researchers, child protection professionals (health and social care), police, legal professionals and adult survivors of CM will be purposefully recruited. We will approach approximately 100 experts, with between 50 and 60 of these anticipated to take part. Participants will rate their agreement with a range of statements relating to operational definitions and types of CM, and free-text comments on each of the statements to give further detail about their responses and areas of uncertainty. Consensus has been defined a priori as ≥70% of the panel agreeing or disagreeing with the statement after the final round. The responses to the open-ended questions will be analysed using a ‘codebook’ approach to thematic analysis, and used to refine the statements between rounds where no consensus is reached.Ethics and dissemination Ethical approval has been granted from the Cardiff University School of Medicine ethics committee (reference number SMREC22/96). Results will be submitted for publication in a peer-reviewed journal and presented at workshops (including for the participants) and international academic conferences. The Euro-CAN network will also be used to disseminate the results, with results briefings and presentations to key public health and other relevant organisations in the field.